PENGARUH PENGGANTIAN BOVINE SERUM ALBUMIN (BSA) DENGAN PUTIH TELUR DALAM PENGENCER DASAR Cep-2 TERHADAP KUALITAS SEMEN KAMBING BOER PADA SIMPAN DINGIN - Ayu Sulvi Istanty; M Ade Salim; Nurul Isnaini; Trinil Susilawati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2017)
The purpose of this research wasinvestigated the substitution effect of Bovine Serum Albumin (BSA) with albumen on CEP-2 diluent to semen quality of Boer goat that was stored at 3-50C. Research was conducted at Reproduction Laboratory and Field Laboratory SumberSekarDau Animal Husbandry Faculty of Brawijaya University from December 2016until January 2017. The materials used for this research were fresh semen from 3,5-4,5 years old Boer goat which was collected with artificial vagina. Semen diluent was divided into two groups, those were P0 (90% CEP-2 + 10% Egg Yolk) and P1 (90% CEP-2 (without BSA) + 0,4% albumen + 10% Egg Yolk). Data of the research were analyzed using paired design t test. The result showed that after eight days of chilled preservation, the sperm motility of P0 was not significantly different with P1 (P>0,05). The average percentage of motility during eight days preservation P0 was higher than P1. The viability between P0 and P1 showed highly significantly difference (P<0,01). The average percentage of viability during eight days preservation P0 was higher than P1. The abnormality between P0 and P1 showed highly significant difference (P<0,01). The average percentage of abnormality between eight dayspreservation P1 was higher than P0. Total motile sperms count after seven days chilled preservation was not significantly different with hope value 40 million motile sperm/ml. The conclusion of this research was the substitution of BSA with albumen could maintain Boer goat semen quality. Keywords : CEP-2, Bovine SerumAlbumin, Semen, Cryoprotectant